1959
DOI: 10.1172/jci103866
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adrenal Steroids and Potassium Depletion on the Elaboration of an Osmotically Concentrated Urine*

Abstract: The investigation reported in this paper is concerned with the effects of desoxycorticosterone acetate (DCA), hydrocortisone and dietary potassium depletion on the elaboration of an osmotically concentrated urine in the hydropenic state. Loeb and his associates (1, 2) demonstrated that dogs maintained on large amounts of DCA develop a diabetes insipidus-like picture. Since then, renal function studies in man (3-5), dogs (6) and rats (7,8) have shown that the ability of the kidney to concentrate the urine is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…These data indicate that kaliopenic isosthenuria can not be attributed solely to ADH refractoriness, unless it is assumed that the permissive action of ADH on water diffusion indirectly regulates medullary blood flow and hence solute retention. A reduced solute concentration in the medulla may prevent efficient operation of the countercurrent multiplier system of the loops of Henle and the collecting ducts by reducing the rate of transfer of water across the tubular cell (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that kaliopenic isosthenuria can not be attributed solely to ADH refractoriness, unless it is assumed that the permissive action of ADH on water diffusion indirectly regulates medullary blood flow and hence solute retention. A reduced solute concentration in the medulla may prevent efficient operation of the countercurrent multiplier system of the loops of Henle and the collecting ducts by reducing the rate of transfer of water across the tubular cell (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…These findings in rodents have precluded a satisfactory explanation for the observation that man and dog can excrete hypotonic final urine during certain experimental and pathological conditions when antidiuretic hormone activity is presumably adequate (3)(4)(5)(6)(7)(8)(9)(10)(11). These observations have been most apparent at high rates of urine flow and solute excretion.…”
mentioning
confidence: 99%
“…Chronic potassium deficiency characteristically results in a decrease in urinary concentrating ability (1)(2)(3). The effects of potassium deficiency on other aspects of renal function are less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of potassium deficiency on other aspects of renal function are less clearly defined. Glomerular filtration rate has been reported to decrease in some studies (1,2), but others have found no consistent change (4). Paraaminohippuric acid (PAH) clearance is often decreased in potassium-depleted patients (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation